Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae) - Neiss, Ulisses Gaspar; Marmels, Jürg De (Zootaxa, 2017)
The new species is described and illustrated on the basis of two reared, subteneral males from Brazil, their larval exuviae, a mature male from French Guiana, a mature female from Venezuela, and a mature female from Surinam. One of the Brazilian males is the holotype (BRAZIL, Amazonas State, Manaus, Reserva Florestal Ducke, BR 174-km 26, trail to Acará creek, 02º55’47”S, 59º58’22”W, 0.7 m elevation, deposited in INPA). The new species (total length 50–54 mm) differs from other small species of same genus by color pattern of thorax, middle and hind tibiae dark with external (dorsal) yellow streak, male cercus with truncated tip lacking apical spine, and male epiproct reaching or slightly surpassing midlength of cercus. The larva, besides of its small size (28–31 mm), has an epiproct with well-developed and slightly diverging apical spines and an unusually long paraproct.